2017
DOI: 10.5213/inj.1732732.366
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Periurethral Calcification According to the Location in Men With Lower Urinary Tract Symptoms and a Small Prostate Volume

Abstract: Purpose:To assess the impact of periurethral calcification (PUC) according to its location on uroflowmetric parameters and urinary symptoms in patients with small prostate volume (PV). Methods: Records were obtained from a prospectively maintained database of first-visit men with lower urinary tract symptoms (LUTS). Patients whose PV was > 30 mL were excluded to elucidate more clearly the impact of PUC on LUTS. A total of 539 patients were enrolled in the study. The prostatic urethra was examined by transrecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 28 publications
0
16
1
Order By: Relevance
“…In these patients, the co-presence of multiple prostatic calcifications having larger prostatic calculi with the diameter over 3 mm has a pathological connection with prostatic inflammatory changes and fibrosis [29,30]. In particular, inflammation of the periurethral area, can contribute, via an excess of collagen deposition and fibrosis in the prostate, to impair urethral function, with urethral stiffness which in turn maximizes induction of LUTS [31][32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these patients, the co-presence of multiple prostatic calcifications having larger prostatic calculi with the diameter over 3 mm has a pathological connection with prostatic inflammatory changes and fibrosis [29,30]. In particular, inflammation of the periurethral area, can contribute, via an excess of collagen deposition and fibrosis in the prostate, to impair urethral function, with urethral stiffness which in turn maximizes induction of LUTS [31][32].…”
Section: Discussionmentioning
confidence: 99%
“…• LUTS encompasses a wide range of symptoms, categorized by the International Continence Society (ICS) as storage, voiding, and postmicturition. The severity of LUTS was assessed using the IPSS, Each of the questions is rated from 0 (not at all) to 5 (almost always), and according to the total symptom score, the severity of LUTS can be graded as mild (0-7), moderate (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) or severe (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), since a total IPSS ≥8 points was considered to indicate the presence of LUTS [18];…”
Section: Inclusion Criteria For Diagnostic Symptomsmentioning
confidence: 99%
“…Previous studies have shown that the prostate volume is weakly correlated with LUTS2,6,20 in patients with a small-volume prostate and BOO. In the present study, neither TPV nor TZV was a predictor of postoperative Qmax, IPSS, IPSS-s, or IPSS-v improvement in patients with a small-volume prostate and BOO.…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, other parameters reflecting the morphological features of the prostate, such as IPP, TZI, PUA, and PUB, were included in our study. These parameters are highly correlated with LUTS in patients with a small prostate 6,20,26. The aim of this study was to investigate the role of these quantitative morphological features in postoperative LUTS improvement in patients with small-volume prostates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation